Epigenetic Regulation and Dietary Control of Triple Negative Breast Cancer - Selmin, Ornella I.; Donovan, Micah G.; Stillwater, Barbara J.; Neumayer, Leigh; Romagnolo, Donato F. (Frontiers in Nutrition, 2020)
Triple negative breast cancer (TNBC) represents a highly heterogeneous group of breast cancers, lacking expression of the estrogen (ER) and progesterone (PR) receptors, and human epidermal growth factor receptor 2 (HER2). TNBC are characterized by a high level of mutation and metastasis, poor clinical outcomes and overall survival. Here, we review the epigenetic mechanisms of regulation involved in cell pathways disrupted in TNBC, with particular emphasis on dietary food components that may be exploited for the development of effective strategies for management of TNBC.